Polymer, resist composition, method for producing substrate having pattern formed thereon, and (meth)acrylic acid ester and method for producing the same

By introducing acid elimination group and lactic acid skeleton units into the polymer of sulfonyl group-containing (meth)acrylic acid ester, and removing high molecular weight substances using a lean solvent precipitation method, the problem of insoluble high molecular weight substances during polymer development is solved, and the polymer is well developed solubility and preparation of high-quality products are achieved.

JP7663111B2Active Publication Date: 2025-04-16MITSUBISHI CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023148444
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-27
Filing Date
2023-09-13
Publication Date
2025-04-16
Estimated Expiration
2040-03-25

AI Technical Summary

Technical Problem

When producing sulfonyl group-containing (meth)acrylic acid esters, high molecular weight products are prone to polymerization, resulting in insoluble in high molecular weight substances during the development process, resulting in defects. Existing methods are difficult to effectively remove high molecular weight substances, affecting product quality.

Method used

Using a polymer containing specific structural units, high-quality sulfonyl group-containing (meth)acrylic acid acid ester is prepared by introducing acid elimination groups and lactic acid skeleton units into the polymer, combined with the use of a lean solvent precipitation method, and high-molecular weight substances are removed.

Benefits of technology

The polymer is developed and solubility is achieved, and the existence of high molecular weight substances is reduced, thereby avoiding defects in the development process and improving the quality and performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663111000001
    Figure 0007663111000001
  • Figure 0007663111000002
    Figure 0007663111000002
  • Figure 0007663111000003
    Figure 0007663111000003
Patent Text Reader

Abstract

To provide a polymer excellent in developer dissolubility, a resist composition containing the polymer, and a method for manufacturing a substrate on which a pattern is formed with the resist composition.SOLUTION: A polymer containing a structural unit (1) based on a monomer represented by formula (1) and having a content of 35 mol% or less of a structural unit based on a monomer having a polycyclic structure. In formula (1), R1 represents a hydrogen atom or a methyl group; A1 represents a linking group containing an ester bond or a single bond, provided that A1 does not have a tertiary carbon atom; Z1 represents an atomic group that forms a sulfur-containing cyclic hydrocarbon group having 3 to 6 carbon atoms, including the carbon atom bonded with A1 and -SO2-.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymer, a resist composition containing the polymer, a method for producing a substrate having a pattern formed thereon using the resist composition, a (meth)acrylic acid ester, and a method for producing the (meth)acrylic acid ester. This application claims priority based on Japanese Patent Application Nos. 2019-059909, 2019-059910, and 2019-060490, filed in Japan on March 27, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] A (meth)acrylic acid ester containing a sulfonyl group (hereinafter, sometimes referred to as a "sulfonyl group-containing (meth)acrylic acid ester") is known as a sulfur-containing monomer. A polymer obtained by homopolymerizing a sulfonyl group-containing (meth)acrylic acid ester or a copolymer obtained by copolymerizing the same with another monomer is used, for example, as a material with high dielectric properties, a material with high refractive index, or a medical adhesive having an anti-inflammatory effect.

[0003] As a method for producing such a sulfonyl group-containing (meth)acrylic ester, a method based on an ester exchange reaction between a (meth)acrylic ester and an alcohol is known (for example, Patent Document 1).

[0004] The exposure light sources used in the lithography used in semiconductor manufacturing are becoming shorter in wavelength, and mass production of semiconductor elements using ArF excimer lasers with a wavelength of 193 nm and higher-energy EUV (extreme ultraviolet) with a wavelength of 13.5 nm as next-generation exposure light sources is progressing. It is desirable for the resist polymers used in these applications to contain a polar group from the viewpoints of adhesion to the substrate and affinity to polar solvents. Conventionally, (meth)acrylic acid esters containing lactone groups have been widely used as monomers containing such polar groups. Sulfonyl group-containing (meth)acrylic esters have high polarity and are expected to be useful as monomers (raw material monomers) for forming resist polymers.

[0005] When a resist polymer is produced using a sulfonyl group-containing (meth)acrylic acid ester as a monomer, if a polymer is mixed into the sulfonyl group-containing (meth)acrylic acid ester, the polymer may become insoluble during development, causing defects. Therefore, it is necessary to reduce the content of the polymer as much as possible.

[0006] Chemically amplified resist compositions are known as resist compositions that can be used effectively in lithography to shorten the wavelength of irradiated light and to make finer patterns. Chemically amplified resist compositions contain a resist polymer from which an acid-leaving group is eliminated by the action of an acid, and a photoacid generator. In recent years, the miniaturization of patterns has progressed rapidly, and there is a demand for the development of resist materials that can further improve various lithography properties such as sensitivity, pattern formability, and line width roughness (LWR).

[0007] The comparative example of Patent Document 2 describes a polymer obtained by polymerizing a mixture containing a monomer represented by formula (a1-1-2): a monomer represented by formula (a2-1-1): a monomer represented by formula (a3-1-1): a monomer represented by formula (I-2) in a molar ratio of 30:20:40:10. It also shows that when a resist pattern was formed using a resist composition containing this polymer and an acid generator, roughness occurred on the side surface of the pattern, resulting in poor line width roughness (LWR).

[0008] [ka] [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2007-153763 A [Patent Document 2] JP 2012-234166 A Summary of the Invention [Problem to be solved by the invention]

[0010] When producing a sulfonyl group-containing (meth)acrylic ester by the transesterification method as described in Patent Document 1, in order to shift the equilibrium to the product side, alcohols such as methanol produced by the reaction are removed by distillation, which requires a high reaction temperature.

[0011] As a result of investigations by the present inventors, it has become clear that sulfonyl group-containing (meth)acrylic acid esters are highly polymerizable, and when exposed to high temperatures in an ester exchange reaction, high molecular weight substances are produced through polymerization of the sulfonyl group-containing (meth)acrylic acid esters. Patent Document 1 describes purifying the product by recrystallization, washing, or the like, but these methods are unable to sufficiently remove the high molecular weight substances.

[0012] Furthermore, in a resist composition that contains a polymer having an acid-leaving group, improvement in LWR can be expected by improving the solubility of the polymer in the developer.

[0013] The present invention has an object to provide a polymer having excellent solubility in a developer, to provide a resist composition containing the polymer, to provide a method for producing a substrate on which a pattern is formed using the resist composition, to provide a (meth)acrylic acid ester having a reduced high molecular weight component, or to provide a method for producing a (meth)acrylic acid ester having a reduced high molecular weight component. [Means for solving the problem]

[0014] The present invention has the following aspects. [1] A polymer comprising a structural unit (1) based on a monomer represented by the following formula (1), in which the content of the structural unit based on a monomer having a polycyclic structure is 35 mol % or less:

[0015] [ka]

[0016] In formula (1), R 1 represents a hydrogen atom or a methyl group; A 1 represents a linking group containing an ester bond or a single bond, provided that A 1 has no tertiary carbon atoms; Z 1 A 1 represents an atomic group which, together with the carbon atom bonded to -SO2-, forms a sulfur-containing cyclic hydrocarbon group having 3 to 6 carbon atoms. [2] The polymer according to [1] above, further comprising a structural unit (2) having an acid-leaving group. [3] The polymer according to the above [2], wherein the structural unit (2) comprises a structural unit (2i) having an acid-leaving group containing an alicyclic hydrocarbon group. [4] The polymer according to [3] above, wherein the structural unit (2) comprises a structural unit (2ii) having an acid-leaving group containing a monocyclic alicyclic hydrocarbon group. [5] The polymer according to any one of [1] to [4] above, wherein the structural unit (1) accounts for 15 mol % or more of all structural units. [6] The polymer according to any one of the above [1] to [5], further comprising a structural unit (3) having a lactone skeleton. [7] A resist composition comprising the polymer of any one of [1] to [6] above, and a compound that generates an acid when exposed to actinic rays or radiation. [8] A method for producing a substrate having a pattern formed thereon, the method comprising the steps of: applying the resist composition according to [7] above onto a surface to be processed of a substrate to form a resist film; exposing the resist film to light; and developing the exposed resist film using a developer.

[0017] [9] A method for producing a (meth)acrylic acid ester represented by the following formula (1x), comprising the following steps 1 and 2: Step 1: A step of obtaining a solution containing a (meth)acrylic acid ester (1x) represented by the following formula (1x) by transesterification between an alcohol represented by the following formula (2x) and a (meth)acrylic acid ester represented by the following formula (3x): Step 2: A step of adding a poor solvent to the solution containing the (meth)acrylic acid ester (1x) obtained in step 1 to precipitate a polymer, and then removing the polymer.

[0018] [ka]

[0019] In formula (1x), R 11 represents a hydrogen atom or a methyl group; A 11 represents a linking group containing an ester bond or a single bond, provided that A 11 has no tertiary carbon atoms; Z 11 A 11 represents an atomic group which, together with the carbon atom bonded to -SO2-, forms a sulfur-containing cyclic hydrocarbon group having 3 to 6 carbon atoms. In formula (2x), Z 11 represents an atomic group forming a sulfur-containing cyclic hydrocarbon group having 3 to 6 carbon atoms, including the carbon atom bonded to the hydroxy group and -SO2-. In formula (3x), R 11 represents a hydrogen atom or a methyl group, R 12 represents a linear or branched alkyl group having 1 to 10 carbon atoms.

[10] The method for producing a (meth)acrylic acid ester according to [9] above, wherein in the step 2, a hydrocarbon solvent is used as the poor solvent.

[0020]

[11] A (meth)acrylic acid ester represented by the following formula (1x):

[0021] [ka]

[0022] In formula (1x), R 11 represents a hydrogen atom or a methyl group; A 11 represents a linking group containing an ester bond or a single bond, provided that A 11 has no tertiary carbon atoms; Z 11 A 11 represents an atomic group which, together with the carbon atom bonded to -SO2-, forms a sulfur-containing cyclic hydrocarbon group having 3 to 6 carbon atoms. Effect of the Invention

[0023] Advantageous Effects of Invention According to the present invention, it is possible to provide a polymer having good solubility in a developer, a resist composition containing the polymer, and a method for producing a substrate having a pattern formed thereon using the resist composition. According to the present invention, it is possible to provide a sulfonyl group-containing (meth)acrylic acid ester with reduced high molecular weight components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the preferred embodiments. The following definitions of terms apply throughout the specification and claims. As used herein, "(meth)acrylic acid" refers to one or both of acrylic acid and methacrylic acid. In this specification, the term "structural unit" refers to an atomic group formed by a polymerization reaction of a monomer. In this specification, the monomer represented by formula (1) may be referred to as monomer (1). The same applies to monomers represented by other formulas. In this specification, the compound represented by formula (1) may be referred to as compound (1). The same applies to compounds represented by other formulas.

[0025] <Polymer> The polymer of this embodiment (hereinafter also referred to as "polymer A") contains a structural unit (1) based on a monomer (1) represented by the following formula (1). The content of the structural unit based on a monomer having a polycyclic structure relative to all structural units of polymer A is 35 mol % or less. It is preferable that the polymer A further contains at least one type of structural unit (2) having an acid-dissociable group. The polymer A may contain at least one type of structural unit other than the structural units (1) and (2). Polymer A is suitable as a resist polymer.

[0026] [Constituent unit (1)] The structural unit (1) is a structural unit formed by cleavage of the ethylenic double bond of the monomer (1).

[0027] [ka]

[0028] In formula (1), R 1 is a hydrogen atom or a methyl group. A 1 is a linking group containing an ester bond or a single bond. 1 does not contain a tertiary carbon atom. 2 -C(=O)O- or -A 3 -OC(=O)- is an example of the A 2 , A 3 A is a divalent chain hydrocarbon group having 1 to 5 carbon atoms. 2 , A 3 The chain hydrocarbon group as A may be linear or branched. 2 , A 3 is preferably an alkylene group having 1 to 3 carbon atoms. 2 , A 3 does not contain a tertiary carbon atom.

[0029] Z 1 A 1is an atomic group forming a sulfur-containing cyclic hydrocarbon group (4- to 7-membered ring) having 3 to 6 carbon atoms, including the carbon atom bonded to -SO2-. From the viewpoint of the stability of the cyclic structure, the number of carbon atoms in this sulfur-containing cyclic hydrocarbon group is preferably 4 to 6. A substituent may be bonded to a carbon atom constituting the sulfur-containing cyclic hydrocarbon group ring. Examples of the substituent include a linear or branched alkyl group having 1 to 10 carbon atoms, a hydroxyl group, an amino group, an aldehyde group, a chloro group, a bromo group, and an iodo group.

[0030] The monomer (1) is preferably an embodiment in which no substituent is bonded to the carbon atom constituting the sulfur-containing cyclic hydrocarbon group ring, or an alkyl group having 1 to 6 carbon atoms is bonded as a substituent. The monomer in this embodiment is represented by the following formula (1').

[0031] [ka]

[0032] In formula (1'), R 1 , A 1 is R in formula (1). 1 , A 1 is the same as: n represents an integer from 1 to 4. 1 The heterocycle bonded to is, for example, a 4-membered ring when n is 1, and a 7-membered ring when n is 4. From the viewpoints of stability and ease of synthesis, n is preferably 2. R 2 represents a substituent bonded to a carbon atom constituting the heterocycle. 2 A 1 It does not bond to the carbon atom that is bonded to m R 2 Each independently represents an alkyl group having 1 to 6 carbon atoms. The alkyl group may be linear or branched. When m is 2 or more, a plurality of R 2 may be the same as or different from each other. m is an integer of 0 or more and (n+1) or less, preferably an integer of 0 or more and n or less, more preferably 0 or 1, and most preferably 0.

[0033] The above A 1 Examples of the group bonded to A include groups represented by the following formulas (1a) to (1d). 1 Represents a bond with .

[0034] [ka]

[0035] The monomer (1) is R 1 is a hydrogen atom or a methyl group, and A 1 is a single bond, and A 1 is preferably bonded to any one of the groups represented by the formulas (1a) to (1d). Among the groups represented by formulae (1a) to (1d), the group represented by formula (1b) is particularly preferred in terms of stability and ease of synthesis. The structural unit (1) contained in the polymer A may be of one type, or of two or more types.

[0036] The content of the structural unit (1) is preferably 15 mol % or more, more preferably 20 mol % or more, and even more preferably 25 mol % or more, based on all the structural units of the polymer A. From the viewpoints of sensitivity and resolution, the upper limit is preferably 70 mol % or less, more preferably 60 mol % or less, and even more preferably 50 mol % or less. For example, relative to all the structural units of polymer A, the structural unit (1) is preferably from 15 to 70 mol %, more preferably from 20 to 60 mol %, even more preferably from 25 to 60 mol %, and particularly preferably from 25 to 50 mol %.

[0037] [Constituent unit (2)] The structural unit (2) is a structural unit based on a monomer having an acid-dissociable group (hereinafter also referred to as monomer (2)). The acid-dissociable group is a group having a bond that is cleaved by the action of an acid, and a part or all of the acid-dissociable group is eliminated from the polymer by cleavage of the bond. In a positive chemically amplified resist composition, the acid-dissociable group of the polymer reacts with an acid and is eliminated in the exposed area by heating after exposure, and the polymer becomes soluble in an alkaline developer. The monomer (2) is preferably a (meth)acrylic acid ester compound. As the (meth)acrylic acid ester compound having an acid-leaving group, known compounds can be used. From the viewpoint of dry etching resistance in the lithography process, the monomer (2) preferably contains a (meth)acrylic acid ester compound having an acid-leaving group containing an alicyclic hydrocarbon group. The alicyclic hydrocarbon group may be monocyclic or polycyclic. The alicyclic hydrocarbon group may contain a heteroatom. The heteroatom is preferably at least one selected from the group consisting of O, S, and N. The number of atoms constituting the ring is preferably 5 to 22. Acrylic acid esters having a tertiary carbon atom at the bond site with the oxygen atom constituting the ester bond of the acrylic acid ester are more preferred because they provide excellent sensitivity and resolution of the resist. Specific examples include monomers (2-1) to (2-4) of the following formulae. In particular, when combined with the structural unit (1), the monomer (2-4) is more preferred because it is more likely to provide an improved effect in terms of solubility in a developer.

[0038] [ka]

[0039] In formulas (2-1) to (2-4), R 31 , R 32 , R 33 , R 34 each independently represents a hydrogen atom or a methyl group. R 21 , R 24 , R 25 each independently represents an alkyl group having 1 to 5 carbon atoms. The alkyl group may be linear or branched. R 22 , R 23 each independently represents an alkyl group having 1 to 3 carbon atoms. The alkyl group may be linear or branched. R 331 , R 332 , R 333 , R 334each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. The alkyl group may be linear or branched. X 1 , X 2 , X 3 , X 4 each independently represents an alkyl group having a carbon number of 1 to 6. The alkyl group may be linear or branched. n1, n2, n3, and n4 each independently represent an integer of 0 to 4. When n1, n2, n3, or n4 is 2 or more, a plurality of X's exist in one molecule. 1 , X 2 , X 3 Or X 4 may be the same as or different from each other. Z 2 , Z 3 each independently represents -O-, -S-, -NH- or -(CH2)k-, where k represents an integer of 1 to 6. q represents 0 or 1. r represents an integer of 0 to 3.

[0040] The structural unit (2) contained in the polymer A may be of one type, or of two or more types. The content of the structural unit (2) is preferably 20 to 80 mol %, more preferably 30 to 70 mol %, and even more preferably 40 to 60 mol %, of all structural units of the polymer A. When it is at least the lower limit of the above range, good sensitivity is likely to be obtained, and when it is at most the upper limit, a good balance as a resist is likely to be obtained, and good adhesion to the substrate is likely to be obtained.

[0041] The structural unit (2) preferably contains a structural unit (2i) having an acid-dissociable group containing an alicyclic hydrocarbon group. The alicyclic hydrocarbon group may be monocyclic or polycyclic. The alicyclic hydrocarbon group may contain a heteroatom. The heteroatom is preferably one or more types selected from the group consisting of O, S, and N. The number of atoms constituting the ring is preferably 5 to 22. The content of the structural unit (2i) relative to the total number of moles of the structural unit (2) is preferably 25 mol% or more, more preferably 35 mol% or more, even more preferably 50 mol% or more, and particularly preferably 75 mol% or more. It may even be 100 mol%. When the content of the structural unit (2i) is at least the lower limit, it is easy to obtain an effect of improving the solubility in a developer when combined with the structural unit (1).

[0042] The structural unit (2) more preferably contains a structural unit (2ii) having an acid-dissociable group containing a monocyclic alicyclic hydrocarbon group. The monocyclic alicyclic hydrocarbon group preferably does not contain a heteroatom. The monocyclic alicyclic hydrocarbon group more preferably contains 5 to 8 atoms constituting the ring, and even more preferably contains 5 to 6 atoms. For example, a structural unit based on the monomer (2-4) is more preferable. The content of the structural unit (2ii) is preferably 25 mol% or more, more preferably 35 mol% or more, even more preferably 50 mol% or more, and particularly preferably 75 mol% or more, based on the total number of moles of the structural unit (2). It may even be 100 mol%. When the content of the structural unit (2ii) is at least the lower limit, it is easy to obtain an effect of improving the solubility in a developer when combined with the structural unit (1).

[0043] The content of the structural units based on monomers having a polycyclic structure relative to all the structural units of the polymer A is 35 mol % or less, and more preferably 30 mol % or less. When the content of the structural units having a polycyclic structure is 35 mol % or less, the polymer A has excellent solubility in a developer.

[0044] [Other building blocks] As the other structural units, structural units known in chemically amplified resist compositions can be used, such as structural units having a lactone skeleton and structural units having a hydrophilic group.

[0045] (Structural unit having a lactone skeleton (hereinafter also referred to as lactone unit)) The lactone skeleton means a monocyclic or polycyclic atomic group containing a ring having -OC(=O)-. The ring having -OC(=O)- may be a ring having -C(=O)-OC(=O)-. The lactone skeleton is preferably a 4- to 20-membered ring, more preferably a 5- to 10-membered ring. The lactone skeleton may be a monocyclic lactone ring, or an aromatic or non-aromatic hydrocarbon ring or heterocyclic ring may be condensed with the lactone ring.

[0046] As the monomer having a lactone skeleton, a (meth)acrylic acid ester compound is preferred. In particular, from the viewpoint of excellent adhesion to a substrate, etc., at least one selected from the group consisting of a (meth)acrylic acid ester having a substituted or unsubstituted δ-valerolactone ring and a (meth)acrylic acid ester having a substituted or unsubstituted γ-butyrolactone ring is preferred, and a monomer having an unsubstituted γ-butyrolactone ring is particularly preferred.

[0047] Specific examples of monomers having a lactone skeleton include β-(meth)acryloyloxy-β-methyl-δ-valerolactone, 4,4-dimethyl-2-methylene-γ-butyrolactone, β-(meth)acryloyloxy-γ-butyrolactone, β-(meth)acryloyloxy-β-methyl-γ-butyrolactone, α-(meth)acryloyloxy-γ-butyrolactone, 2-(1-(meth)acryloyloxy)ethyl-4-butanolide, (meth)acrylic acid pantoyl lactone, 5-(meth)acryloyloxy-2,6-norbornane carbolactone, 8-methacryloxy-4-oxatricyclo[5.2.1.0 2,6 ]Decan-3-one, 9-methacryloxy-4-oxatricyclo[5.2.1.0 2,6 ]decan-3-one, etc. The lactone unit contained in polymer A may be of one type or of two or more types.

[0048] When polymer A contains a lactone unit, the content thereof is preferably 10 to 70 mol %, more preferably 20 to 60 mol %, and even more preferably 30 to 50 mol %, based on the total constitutional units of polymer A. When within the above range, the effect of improving adhesion to a substrate is easily obtained.

[0049] (Structural unit having a hydrophilic group (hereinafter also referred to as hydrophilic unit)) In this specification, the "hydrophilic group" is one or more selected from the group consisting of -C(CF3)2-OH, a hydroxy group, a cyano group, a methoxy group, a carboxy group, and an amino group. As the monomer having a hydrophilic group, a (meth)acrylic acid ester compound and a styrene derivative having a hydroxy group are preferable.

[0050] Specific examples of monomers having a hydrophilic group include (meth)acrylic acid, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxy-n-propyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 3-hydroxyadamantyl (meth)acrylate, 2- or 3-cyano-5-norbornyl (meth)acrylate, 2-cyanomethyl-2-adamantyl (meth)acrylate, p-hydroxystyrene, and dihydroxystyrene. In terms of adhesion to a substrate, etc., 3-hydroxyadamantyl (meth)acrylate, 3,5-dihydroxyadamantyl (meth)acrylate, 2- or 3-cyano-5-norbornyl (meth)acrylate, 2-cyanomethyl-2-adamantyl (meth)acrylate, and the like are preferred. The hydrophilic units contained in the polymer A may be of one type or of two or more types.

[0051] The structural unit having a hydrophilic group contributes to improving the wettability of the polymer A to a developer. The content of the structural unit having a hydrophilic group relative to all structural units of the polymer A is preferably 0 to 40 mol%, more preferably 5 to 30 mol%, and even more preferably 10 to 20 mol%. When it is within the above range, a good balance as a resist is easily obtained.

[0052] Preferred embodiments of the polymer A include the following embodiments (i) to (iv). (i) A polymer comprising the structural unit (1) and the structural unit (2), in which, based on all structural units, the structural unit (1) accounts for 15 to 70 mol %, the structural unit (2) accounts for 20 to 80 mol %, and the total of these is 35 to 100 mol %. (ii) A polymer comprising structural units (1), structural units (2), and lactone units, in which, based on all structural units, structural units (1) account for 15 to 70 mol %, lactone units for 10 to 70 mol %, the total of structural units (1) and lactone units for 25 to 85 mol %, structural units (2) for 20 to 80 mol %, and the total of structural units (1), structural units (2) and lactone units for 45 to 100 mol %. (iii) A polymer comprising a structural unit (1), a structural unit (2), and a hydrophilic unit, wherein, based on all structural units, the structural unit (1) accounts for 15 to 70 mol %, the hydrophilic unit accounts for 0 to 40 mol %, the total of the structural unit (1) and the hydrophilic unit accounts for 15 to 80 mol %, the structural unit (2) accounts for 20 to 80 mol %, and the total of the structural unit (1), the structural unit (2), and the hydrophilic unit accounts for 35 to 100 mol %. (iv) A polymer comprising structural units (1), structural units (2), lactone units and hydrophilic units, wherein, based on all structural units, structural units (1) account for 15 to 70 mol%, lactone units for 10 to 70 mol%, hydrophilic units for 0 to 40 mol%, the total of structural units (1), lactone units and hydrophilic units for 25 to 85 mol%, structural units (2) for 25 to 80 mol%, and the total of structural units (1), structural units (2), lactone units and hydrophilic units for 50 to 100 mol%.

[0053] Polymer A can be produced, for example, by a solution polymerization method in which monomers are radically polymerized in the presence of a polymerization solvent using a polymerization initiator. The weight average molecular weight of polymer A is preferably from 1,000 to 100,000, more preferably from 3,000 to 50,000, and further preferably from 5,000 to 30,000.

[0054] <Resist Composition> The resist composition of this embodiment preferably contains a polymer A, a resist solvent, and a compound that generates an acid upon irradiation with actinic rays or radiation. The polymer A may be one type, or two or more types may be used in combination. The content of polymer A in the resist composition (excluding the solvent) is not particularly limited, but is preferably from 70 to 99.9 mass %.

[0055] Examples of the resist solvent include cyclopentanone, cyclohexanone, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), etc. The resist solvent may be one type, or two or more types may be used in combination. The amount of the resist solvent used depends on the thickness of the resist film to be formed, but is preferably in the range of 100 to 10,000 parts by mass per 100 parts by mass of Polymer A.

[0056] The compound that generates an acid upon irradiation with actinic rays or radiation can be arbitrarily selected from those usable as a photoacid generator for a chemically amplified resist composition. The photoacid generator may be used alone or in combination of two or more kinds. Examples of the photoacid generator include an onium salt compound, a sulfonimide compound, a sulfone compound, a sulfonate compound, a quinone diazide compound, and a diazomethane compound. The amount of the photoacid generator used is preferably from 0.1 to 20 parts by mass, and more preferably from 0.5 to 10 parts by mass, based on 100 parts by mass of the polymer A.

[0057] The resist composition may contain various additives, as necessary, such as a nitrogen-containing compound, an acid compound (an organic carboxylic acid, a phosphorus oxo acid or a derivative thereof), a surfactant, other quenchers, a sensitizer, an antihalation agent, a storage stabilizer, an antifoaming agent, etc. Any additive known in the field of resist compositions can be used as the additives.

[0058] <Method for manufacturing a substrate having a pattern formed thereon> An example of a method for manufacturing a substrate on which a pattern of this embodiment is formed will be described. First, a resist composition is applied onto the surface (working surface) of a substrate to be processed such as a silicon wafer by spin coating, etc. Then, the substrate to be processed onto which the resist composition has been applied is dried by baking treatment (pre-bake), etc., to form a resist film on the substrate. Next, the resist film is irradiated with light having a wavelength of 250 nm or less through a photomask to form a latent image (exposure). As the irradiating light, KrF excimer laser, ArF excimer laser, F2 excimer laser, and EUV excimer laser are preferable, and ArF excimer laser is particularly preferable. Electron beam irradiation may also be used. In addition, immersion exposure may be performed by irradiating light with a high refractive index liquid such as pure water, perfluoro-2-butyltetrahydrofuran, or perfluorotrialkylamine interposed between the resist film and the final lens of an exposure tool.

[0059] After exposure, the resist is appropriately heat-treated (post-exposure bake, PEB) and a developer is placed in contact with the resist film to dissolve part of the resist film. In a positive-tone development process, the exposed area is dissolved and removed using an alkaline developer. In polymer A, the bond of the acid-releasable group is cleaved by the acid generated by exposure to light, and the dissolution rate of the exposed area in an alkaline developer increases. The alkaline developer may be an aqueous alkaline solution, such as an aqueous solution of inorganic alkalis, such as sodium hydroxide, potassium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, or ammonia water; primary amines, such as ethylamine or n-propylamine; secondary amines, such as diethylamine or di-n-butylamine; tertiary amines, such as triethylamine or methyldiethylamine; alcohol amines, such as dimethylethanolamine or triethanolamine; quaternary ammonium salts, such as tetramethylammonium hydroxide or tetraethylammonium hydroxide; or cyclic amines, such as pyrrole or piheridine. After development, the substrate is appropriately rinsed with pure water, etc. In this manner, a resist pattern is formed on the substrate to be processed. The substrate on which the resist pattern has been formed is appropriately heat-treated (post-baked) to strengthen the resist, and the portions without resist are selectively dry-etched. After the dry etching, the resist is removed with a stripping agent to obtain a substrate on which a fine pattern is formed.

[0060] <(Meth)acrylic acid ester> The (meth)acrylic acid ester of the present embodiment is a sulfonyl group-containing (meth)acrylic acid ester (compound (1x)) represented by the following formula (1x), and is characterized in that the content of high molecular weight substances having a molecular weight of 5,000 or more is 0.1 mass% or less.

[0061] [ka]

[0062] In formula (1x), R 11 represents a hydrogen atom or a methyl group; A 11 represents a linking group containing an ester bond or a single bond, provided that A 11 has no tertiary carbon atoms; Z 11 A 11 represents an atomic group which, together with the carbon atom bonded to -SO2-, forms a sulfur-containing cyclic hydrocarbon group having 3 to 6 carbon atoms.

[0063] Here, the (meth)acrylic acid ester of this embodiment, in which the content of high molecular weight substances having a molecular weight of 5000 or more is specified, may be referred to as a "(meth)acrylic acid ester composition" rather than a "(meth)acrylic acid ester". However, in the (meth)acrylic acid ester of this embodiment, the high molecular weight substance having a molecular weight of 5000 or more (hereinafter, may be simply referred to as a "high molecular weight substance") is contained in an extremely small amount of 0.1 mass% or less, or the content is below the detection limit and is almost not contained. In addition, when the content of high molecular weight substances is 0.1 mass% or less, it is called a "(meth)acrylic acid ester product" and is further used for various purposes. Therefore, in this embodiment, such a (meth)acrylic acid ester containing an extremely small amount of high molecular weight substances or almost no high molecular weight substances is referred to as a "(meth)acrylic acid ester". As described above, a polymer content of 0.1% by mass or less means below the detection limit in the analysis of polymers, and essentially includes a polymer content of 0% by mass.

[0064] [Compound (1x)] In the formula (1x), A 11 is a linking group containing an ester bond or a single bond. 11 has no tertiary carbon atoms. 11 The linking group containing an ester bond as the above A 1 The linking group containing an ester bond is the same as that of the linking group A. 11 is preferably a single bond from the viewpoints of availability of raw materials and ease of synthesis. R 11 is a hydrogen atom or a methyl group, and is preferably a methyl group.

[0065] Z 11 A 11 is an atomic group forming a sulfur-containing cyclic hydrocarbon group (4- to 7-membered ring) having 3 to 6 carbon atoms, including the carbon atom bonded to -SO2-. From the viewpoint of the stability of the cyclic structure, the number of carbon atoms in this sulfur-containing cyclic hydrocarbon group is preferably 4 to 6. A substituent may be bonded to a carbon atom constituting the sulfur-containing cyclic hydrocarbon group ring. Examples of the substituent include a linear or branched alkyl group having 1 to 10 carbon atoms, a hydroxyl group, an amino group, an aldehyde group, a chloro group, a bromo group, and an iodo group.

[0066] From the viewpoints of availability of raw materials and stability of the compound, the sulfur-containing cyclic hydrocarbon group is more preferably a 2-sulfolane or 3-sulfolane structure in which the ring containing the sulfonyl group is a 5-membered ring, and of these, the 3-sulfolane structure is most preferred. The most preferred compound (1x) is 3-sulfolanyl methacrylate.

[0067] [High molecular weight substance] In this embodiment, the content of the high molecular weight substance in the (meth)acrylic acid ester can be analyzed by the method described in the Examples section below, and the detection limit is 0.03 mass % or less.

[0068] The high molecular weight substance in the (meth)acrylic acid ester of this embodiment is a high molecular weight substance produced by polymerization or copolymerization of the sulfonyl group-containing (meth)acrylic acid ester, which is the target product (compound (1x)), or the compound (3x), which is a raw material for producing compound (1x), due to its high polymerizability in step 1 of the production method of the (meth)acrylic acid ester described later. The molecular weight of the high molecular weight substance is 5,000 or more, and the weight average molecular weight (Mw) measured by the method described in the Examples section below is 3×10 5 ~6×10 5 If the molecular weight of the high molecular weight substance is less than 5000, it is soluble in the solvent and will remain in the mother liquor and be removed by recrystallization or the like, and therefore will not be subject to removal in step 2 described below.

[0069] The content of high molecular weight substances in the (meth)acrylic acid ester of this embodiment is preferably 0.1% by mass or less, the lower the better, preferably 0.05% by mass or less, more preferably 0.03% by mass or less, and most preferably below the detection limit.

[0070] The (meth)acrylic acid ester of this embodiment having such a reduced content of high molecular weight components can be produced by the production method of the (meth)acrylic acid ester of this embodiment described below.

[0071] [Application] The (meth)acrylic acid ester of the present embodiment, which has a reduced content of polymers, can exhibit the excellent properties inherent to sulfonyl group-containing (meth)acrylic acid esters without being affected by polymers, and is useful in a wide range of applications, such as plastic raw materials, paints, and adhesives. In particular, the sulfonyl group-containing (meth)acrylic acid ester of this embodiment is useful in resist applications, for example as a monomer constituting an ArF resist polymer. By using a monomer with a reduced content of high molecular weight components, the lithography properties of the resist polymer can be improved. For example, the solubility and developability of the resist polymer can be improved, and defects during development due to the high molecular weight components can be prevented. In addition, the adhesion to the substrate and the affinity to polar solvents can be improved due to the sulfonyl group. The sulfonyl group-containing (meth)acrylic acid ester of the present embodiment can be suitably used as the monomer (1) constituting the polymer A.

[0072] <Method of producing (meth)acrylic acid ester> The method for producing a (meth)acrylic acid ester according to the present embodiment is a method for producing a (meth)acrylic acid ester represented by the formula (1x) and includes the following steps 1 and 2.

[0073] Step 1: A step of obtaining a solution containing a (meth)acrylic acid ester represented by the following formula (1x) by transesterification of an alcohol represented by the following formula (2x) with a (meth)acrylic acid ester represented by the following formula (3x):

[0074] [ka]

[0075] In formula (2x), Z 11 represents an atomic group forming a sulfur-containing cyclic hydrocarbon group having 3 to 6 carbon atoms, including the carbon atom bonded to the hydroxy group and -SO2-.

[0076] [ka]

[0077] In formula (3x), R 11 represents a hydrogen atom or a methyl group, R 12 represents a linear or branched alkyl group having 1 to 10 carbon atoms.

[0078] Step 2: A step of adding a poor solvent to the solution containing the (meth)acrylic acid ester represented by the formula (1x) obtained in step 1 to precipitate a polymer, and then removing the polymer.

[0079] [Step 1: Reaction step] In step 1, an alcohol compound (2x) represented by the above formula (2x) is reacted with a (meth)acrylic acid ester compound (3x) represented by the above formula (3x) to obtain a compound (1x).

[0080] In compound (2x), Z 11 is an atomic group forming a sulfur-containing cyclic hydrocarbon group having 3 to 6 carbon atoms, including the carbon atom bonded to the hydroxy group and -SO2-. From the viewpoint of the stability of the cyclic structure, the number of carbon atoms in this sulfur-containing cyclic hydrocarbon group is preferably 4 to 6. In addition, a substituent may be bonded to a carbon atom constituting the ring of this sulfur-containing cyclic hydrocarbon group. Examples of the substituent include a linear or branched alkyl group having 1 to 10 carbon atoms, a hydroxy group, an amino group, an aldehyde group, a chloro group, a bromo group, and an iodo group. From the viewpoint of availability of raw materials, the sulfur-containing cyclic hydrocarbon group is preferably a 2-sulfolane or 3-sulfolane structure in which the ring containing the sulfonyl group is a five-membered ring, and among these, the 3-sulfolane structure is most preferred. The compound (2x) is most preferably 3-hydroxysulfolane.

[0081] In compound (3x), R 11 is a hydrogen atom or a methyl group, and is preferably a methyl group.

[0082] R 12 is a linear or branched alkyl group having 1 to 10 carbon atoms. Examples of the linear or branched alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, a normal propyl group, an isopropyl group, a normal butyl group, an isobutyl group, a t-butyl group, a normal pentyl group, a normal hexyl group, and a 2-ethylhexyl group. In the transesterification reaction, it is necessary to remove the alcohol derived from the raw material ester by distillation, so it is preferable that the boiling point of the by-product alcohol generated in the transesterification reaction is low. 12 is preferably a methyl group. That is, the compound (3x) is preferably methyl acrylate or methyl methacrylate.

[0083] In step 1, compound (1x) is produced by transesterification. The conditions for the transesterification are not particularly limited, and the transesterification may be carried out by a known method. For example, JP-A-2007-153763 discloses a method of reacting 3-hydroxysulfolane with methyl methacrylate to obtain 3-sulfolanyl methacrylate.

[0084] In order to obtain compound (1x) in good yield, it is preferable to use compound (2x) after dehydration. As a method for dehydration, a method is preferable in which compound (2x) is dissolved in an organic solvent, heated, and water is removed by azeotropic distillation of the organic solvent and water. As an azeotropic organic solvent, benzene, toluene, ethylbenzene, methyl ethyl ketone, 1,4-dioxane, hexane, cyclohexane, etc. can be used. In addition, when compound (3x) forms an azeotrope with water, compound (2x) can be dissolved in compound (3x) and dehydrated by azeotropic distillation.

[0085] In the transesterification reaction, a catalyst may or may not be used. In order to obtain the compound (1x) in good yield, it is preferable to use a catalyst. When a catalyst is used, a titanium catalyst or a tin catalyst can be used. Examples of the titanium catalyst include tetramethoxytitanium, tetraethoxytitanium, tetranormalpropoxytitanium, tetraisopropoxytitanium, tetranormalbutoxytitanium, and tetraisobutoxytitanium. Examples of the tin catalyst include dinormalbutyltin oxide, dinormaloctyltin oxide, and di-2-ethylhexyltin oxide. In view of the removability of the catalyst after the reaction, it is preferable to use a titanium catalyst.

[0086] The amount of the catalyst used is preferably 0.001 mol or more, more preferably 0.01 mol or more, per mol of compound (2x) from the viewpoint of efficient production of compound (1x). The amount of the catalyst used is preferably 0.05 mol or less, more preferably 0.03 mol or less, per mol of compound (2x) from the viewpoint of catalyst removability and cost. The transesterification catalyst may be added at once or in portions. For example, the amount of the catalyst used is preferably 0.001 to 0.05 mol, and more preferably 0.01 to 0.03 mol, relative to 1 mol of compound (2x).

[0087] The amount of compound (3x) used in the transesterification reaction is not particularly limited, but from the viewpoint of obtaining compound (1x) in a good yield, it is preferably 0.5 mol or more per mol of compound (2x), more preferably 0.8 mol or more, and even more preferably 1.0 mol or more. In particular, when removing by-product alcohol by azeotropy with compound (3x), if the amount of compound (3x) used is small, the by-product alcohol cannot be sufficiently removed, and the reaction rate may decrease. In addition, from the viewpoint of reducing the efficiency of the vessel in the transesterification reaction and the load on the post-reaction treatment process, the amount of compound (3x) used is preferably 12 mol or less per mol of compound (2x), more preferably 10 mol or less, and even more preferably 8 mol or less. For example, the amount of compound (3x) used is preferably 0.5 to 12 mol, more preferably 0.8 to 10 mol, and even more preferably 1 to 8 mol, per 1 mol of compound (2x).

[0088] It is preferable to add a polymerization inhibitor to the reaction system in order to suppress the polymerization of compound (3x) or compound (1x). The type of polymerization inhibitor is not particularly limited, and one type or two or more types may be used.

[0089] Examples of the polymerization inhibitor include phenolic compounds such as hydroquinone, p-methoxyphenol, 2,4-dimethyl-6-tert-butylphenol, 2,6-tert-butyl-4-methylphenol, tert-butylcatechol, and 2,6-di-tert-butyl-4-methylphenol; amine compounds such as N,N-diisopropyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and N,N-di-2-naphthylparaphenylenediamine; and N-oxyl compounds such as 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl, 4-benzoyloxy-2,2,6,6-tetramethylpiperidine-N-oxyl, 4-acetamido-2,2,6,6-tetramethylpiperidine-N-oxyl, and bis(1-oxyl-2,2,6,6-tetramethylpiperidin-4-yl)sebacate.

[0090] It is also preferable to bubble an oxygen-containing gas during the ester exchange reaction in order to prevent polymerization. The amount of oxygen-containing gas to be introduced can be appropriately set. It is particularly preferable to use air as the oxygen-containing gas.

[0091] The temperature of the transesterification reaction is not particularly limited, but in order to remove by-produced alcohol and improve the reaction rate, it is preferably 30° C. or higher, more preferably 60° C. or higher, and in order to suppress the polymerization of compound (3x) and compound (1x), it is preferably 160° C. or lower, more preferably 140° C. or lower. For example, the temperature of the transesterification reaction is preferably from 30 to 160°C, and more preferably from 60 to 140°C.

[0092] The time for the transesterification reaction is preferably 0.5 hours or more, more preferably 1 hour or more, from the viewpoint of efficiently obtaining compound (1x), and is preferably 50 hours or less, more preferably 30 hours or less, in order to suppress polymerization of compound (3x) or compound (1x). For example, the time for the transesterification reaction is preferably from 0.5 to 50 hours, more preferably from 1 to 30 hours.

[0093] When a catalyst is used as a post-treatment after the reaction, an operation for deactivating the catalyst may be performed. In particular, when the compound (1x) is used for a resist, it is preferable to reduce the inclusion of metal as much as possible. For this purpose, when a metal is used as a catalyst, it is preferable to deactivate and remove the catalyst. For example, the following method can be mentioned as a method for this purpose. That is, after cooling the reaction solution to about 70°C or less while stirring, water in an amount equal to or greater than the amount of the catalyst added, an adsorbent, and Celite as a filter aid are added to deactivate and precipitate the catalyst as a metal oxide. After the addition is completed, stirring is continued for about 1 to 5 hours. The precipitated metal oxide can be removed by pressure filtration, reduced pressure filtration, or the like.

[0094] [Step 2: Purification step] In step 2, a poor solvent is added to the solution containing the compound (1x) produced in step 1 to precipitate a polymer, and the precipitated polymer is removed. Note that the precipitation of the polymer by the poor solvent in step 2 is performed without precipitating the compound (1x), and is different from the washing operation and recrystallization operation described below in which the polymer is not precipitated.

[0095] The poor solvent to be added is not particularly limited, and examples thereof include hydrocarbon solvents such as pentane, hexane, heptane, cyclopentane, cyclohexane, octane, toluene, and xylene, ether solvents such as diethyl ether, diisopropyl ether, t-butyl methyl ether, tetrahydrofuran, and dioxane, ester solvents such as ethyl acetate, butyl acetate, methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, and butyl methacrylate, and alcohol solvents such as methanol, ethanol, and 2-propanol. One type of poor solvent may be used alone, or two or more types may be mixed and used. It is more preferable to use a hydrocarbon solvent in which the solubility of high molecular weight substances is low. Among them, saturated hydrocarbon solvents having 5 to 7 carbon atoms, such as pentane, hexane, and heptane, are more preferable because they can be easily removed by distillation or the like.

[0096] The amount of poor solvent added can be appropriately determined depending on the amount and solubility of the polymer. In order to reduce the solubility of the polymer and precipitate it, the amount is preferably 0.2 times or more by mass, more preferably 0.5 times or more by mass, relative to the mass of the compound (2x) used in the reaction. In addition, in terms of economy and kettle efficiency, the amount is preferably 5 times or less by mass, more preferably 3 times or less by mass, relative to the mass of the compound (2x) used in the reaction. For example, the amount of the poor solvent added is preferably 0.2 to 5 times, and more preferably 0.5 to 3 times, the mass of the compound (2x) used in the reaction.

[0097] The method for removing the precipitated high molecular weight substances is not particularly limited, and examples thereof include separation of the distillation residue, pressure filtration, vacuum filtration, centrifugation, etc. An appropriate method may be used in consideration of the boiling point and properties of compound (1x), the scale, the amount of high molecular weight substances, etc. In order not to generate high molecular weight substances again in the removal process, it is preferable to use pressure filtration, vacuum filtration, and centrifugation, which are methods that do not involve heating. After the separation of the high molecular weight components, the poor solvent may be removed by concentrating the mixture by distillation under reduced pressure or the like.

[0098] Step 2 may include a purification operation of compound (1x) as necessary. Methods for purifying compound (1x) include washing, heat treatment, filtration, distillation, recrystallization, and the like. These may be carried out alone or in combination of two or more. Purification may be carried out before or after the step of precipitating the polymeric substance, or may be carried out both before and after the step.

[0099] Since the compound (2x) has a sulfonyl group, it is highly polar and easily soluble in water. Therefore, the compound (2x) can be removed into the water layer by washing with water or an aqueous solution containing 5 to 30 mass % of an inorganic salt such as sodium chloride, ammonium sulfate, or sodium sulfate as a washing solution. The number of washings can be appropriately determined. From the viewpoint of reducing the inclusion of metals in the compound (1x), it is preferable to include a step of washing with water.

[0100] The washing may be performed without adding a solvent, or may be diluted with a solvent. In order to reduce hydrolysis of compound (1x) or outflow into the water layer, dilution with a solvent is preferable. The solvent is not particularly limited, and hydrocarbon solvents such as pentane, hexane, heptane, cyclopentane, cyclohexane, octane, toluene, and xylene, ether solvents such as diethyl ether, diisopropyl ether, t-butyl methyl ether, tetrahydrofuran, and dioxane, and ester solvents such as ethyl acetate, butyl acetate, methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, and butyl methacrylate can be used. These solvents may be used alone or in combination of two or more. The amount of the solvent used can be appropriately determined depending on the solubility of compound (1x) and the amount of the washing solution.

[0101] When purifying compound (1x) by distillation, it is preferable to add a polymerization inhibitor and carry out the purification at a vacuum of 1.3 kPa (10 mmHg) or less while appropriately introducing an oxygen-containing gas such as air. In particular, it is preferable to carry out the purification by a method such as thin-film distillation, since it has little thermal history.

[0102] When purifying compound (1x) by recrystallization, a solvent is used that dissolves compound (1x) between room temperature and 40° C. and precipitates crystals by cooling to room temperature or lower. As the solvent used for recrystallization, alcohol-based solvents such as methanol, ethanol, isopropanol, butanol, ester-based solvents such as ethyl acetate, butyl acetate, methyl methacrylate, and ether-based solvents such as diethyl ether, diisopropyl ether, and t-butyl methyl ether can be used alone or in mixture. In order to improve the recovery rate of recrystallization, hydrocarbon-based solvents such as hexane, octane, and heptane, which do not easily dissolve crystals, halogen-based solvents such as chloroform, dichloroethane, and dichloromethane, and water can also be mixed with the alcohol-based solvent, ester-based solvent, or ether-based solvent. In terms of ease of solvent reuse, it is preferable to use an alcohol-based solvent alone. In terms of appropriate slurry concentration when crystals are precipitated and improving the recovery rate, a mixed solvent of an alcohol-based solvent and a hydrocarbon-based solvent is more preferable. The slurry concentration is preferably 25% by mass or less, more preferably 20% by mass or less, from the viewpoints of suppressing an increase in viscosity and improving processability, and is preferably 5% by mass or more, more preferably 10% by mass or more, from the viewpoints of economy and kettle efficiency. For example, the slurry concentration is preferably from 5 to 25% by mass, and more preferably from 10 to 20% by mass.

[0103] In recrystallization, it is preferable to dissolve compound (1x) in a solvent at 30°C or higher, gradually cool it, and add seed crystals when the internal temperature reaches 5 to 10°C to promote crystallization. As the crystallization proceeds, the internal temperature rises due to latent heat, but the crystals are separated when the internal temperature reaches 10°C or lower by cooling. The crystals can be separated using a centrifugal filter, a pressure filter, or the like. After separation of the crystals, they are washed with a solvent. After recrystallization, it is preferable to separate the crystals using a solvent that is miscible or soluble in water, and then wash the wet crystal cake with water. This makes it possible to remove most of the solvent attached to the crystals, and there is almost no possibility of the wet crystals melting even if their temperature rises to around room temperature. EXAMPLES

[0104] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.

[0105] Example (I) The reaction was monitored by gas chromatography. <Method for measuring weight average molecular weight> The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the polymer were determined in terms of polystyrene by gel permeation chromatography using tetrahydrofuran (THF) as the eluent.

[0106] <Method for measuring copolymer composition ratio> For the polymers obtained in each example, the composition ratio (unit: mol%) of the structural units based on each monomer is as follows: 1 It was determined by H-NMR measurement. In this measurement, a superconducting FT (Fourier transform)-NMR device, ECS-400 type, manufactured by JEOL Ltd., was used, and about 5 mass% sample solution (solvent is deuterated chloroform) was placed in a sample tube with a diameter of 5 mm, and 64 integrations were performed in single pulse mode at an observation frequency of 400 MHz. The measurement temperature was 60°C.

[0107] <Method for evaluating developer solubility (method for measuring turbidity)> Using a turbidity meter (manufactured by Orbeco-Hellige, product name: TB200), the turbidity Th(80) and turbidity Tm(80) were measured by the following measurement method. Th(80) is an index of solubility in organic solvents with low polarity, and Tm(80) is an index of solubility in organic solvents with high polarity. Higher turbidity indicates lower solubility in organic solvents. In other words, higher turbidity indicates higher polarity and tends to be more soluble in alkaline developer.

[0108] [Method of measuring turbidity Th(80)] (1) A polymer to be measured is dissolved in a mixed solvent of PGMEA / γ-butyrolactone = 75 / 25 mass % to prepare a PGMEA / γ-butyrolactone solution with a concentration of 20 mass % (hereinafter referred to as a sample solution). (2) n-heptane is added to the sample solution prepared in (1) above to prepare a mixed solution, and the amount of n-heptane to be added to the sample solution (Xh mass%) when the turbidity of the mixed solution becomes 10 NTU is determined. (3) n-heptane in an amount equivalent to 80% of the Xh mass % is added to the sample solution prepared in (1) above, and the mixture is stirred at 25°C for 4 hours to obtain a measurement solution. (4) The turbidity of the measurement solution at 25°C is Th(80). [Method of measuring turbidity Tm(80)] (5) Methanol is added to the sample solution prepared in (1) above to prepare a mixed solution, and the amount of methanol to be added to the sample solution (Xm mass%) when the turbidity of the mixed solution becomes 5.0 NTU is determined. (6) Methanol in an amount equivalent to 80% of the Xm mass % is added to the sample solution prepared in (1) above, and stirred at 25°C for 4 hours to obtain a measurement solution. (7) The turbidity of the measurement solution at 25°C is Tm(80).

[0109] In the following examples and comparative examples, the following monomers (m1) to (m7) were used.

[0110] [ka]

[0111] [ka]

[0112] [Example 1-1] In a flask equipped with a nitrogen inlet, a stirrer, a condenser, and a thermometer, 8.1 parts by mass of PGMEA and 32.5 parts by mass of γ-butyrolactone were placed under a nitrogen atmosphere, and the temperature of the water bath was raised to 80° C. while stirring. Then, the following mixture 1 was dropped into the flask from the dropping funnel over 4 hours, and the temperature was maintained at 80° C. for another 3 hours to obtain a reaction solution. (Composition of Mixture 1) Monomer (m1) 8.17 parts by mass (20 mol%), Monomer (m2) 10.20 parts by mass (30 mol%), Monomer (m3) 13.44 parts by mass (40 mol%), Monomer (m4) 4.72 parts by mass (10 mol%), Solvent: 8.9 parts by weight of PGMEA, 35.7 parts by weight of γ-butyrolactone, and Polymerization initiator: dimethyl-2,2'-azobisisobutyrate (V601 (product name) manufactured by Wako Pure Chemical Industries, Ltd.) 3.91 parts by mass.

[0113] The obtained reaction solution was dropped into about 10 times the amount of a mixed solvent of methanol and water (methanol / water = 80 / 20 volume ratio) while stirring, and a white precipitate was obtained. The precipitate was filtered and poured again into the same amount of methanol as above, and the precipitate was washed while stirring. The washed precipitate was then filtered to obtain a polymer wet powder, which was dried under reduced pressure at 60 ° C for about 36 hours to obtain a dry powdered polymer. The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the obtained polymer are shown in Table 1 (the same applies hereinafter). The turbidity of the resulting polymer was measured by the above-mentioned method, and the results are shown in Table 1 (hereinafter the same). The copolymerization composition ratios shown in Table 1 are the feed ratios, but when the copolymerization composition ratios of the obtained polymer were measured by the method described above, they were found to be 20.2 mol% for the structural unit (m1), 30.1 mol% for the structural unit (m2), 39.7 mol% for the structural unit (m3), and 10.0 mol% for the structural unit (m4), which were almost the same as the feed ratios.

[0114] 15.0 parts by mass of the dry powdery polymer obtained above, 105.0 parts by mass of PGMEA, and 0.3 parts by mass of triphenylsulfonium triflate as a photoacid generator were mixed to prepare a homogeneous solution, which was then filtered through a membrane filter having a pore size of 0.1 μm to prepare a resist composition.

[0115] [Example 1-2, Comparative Example 1-1] The monomer charging composition in Example 1-1 was changed as shown in Table 1. A polymer was produced and evaluated in the same manner as in Example 1-1 except for the above. Furthermore, using the obtained polymer, a resist composition was produced in the same manner as in Example 1-1.

[0116] [Comparative Examples 2-1 and 2-2] The monomer charging composition in Example 1-1 was changed as shown in Table 1. A polymer was produced and evaluated in the same manner as in Example 1-1 except for the above. Furthermore, using the obtained polymer, a resist composition was produced in the same manner as in Example 1-1.

[0117] [Examples 3-1, 4-1, Comparative Example 3-1] The monomer charging composition in Example 1-1 was changed as shown in Table 1. A polymer was produced and evaluated in the same manner as in Example 1-1 except for the above. Furthermore, using the obtained polymer, a resist composition was produced in the same manner as in Example 1-1.

[0118] [Table 1]

[0119] As shown in Table 1, the polymers of Examples 1-1, 1-2, 3-1, and 4-1 have high turbidity, which indicates that they have high polarity and excellent solubility in an alkaline developer.

[0120] Example (II) In the following Examples and Comparative Examples, 3-hydroxysulfolane synthesized according to the method described in Patent Document 1 (JP-A-2007-153763) was used. As the methyl methacrylate, Acryester M (product name) manufactured by Mitsubishi Chemical Corporation was used. The tetrabutoxytitanium used was manufactured by Kanto Chemical Co., Ltd. 4-Hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl was used, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. The Celite used was Celite 545 (product name) manufactured by Kishida Chemical Co., Ltd.

[0121] The reaction rate in the transesterification reaction was calculated from the peak area measured by gas chromatography (hereinafter referred to as "GC"; apparatus: Agilent 6890GC, Agilent Technologies, Inc.; column: HP-5) using the following formula. Response rate (%) = (A / B) x 100 Here, A represents the quantitative value of compound (1) based on the calibration curve, and B represents the sum of the quantitative values ​​of compounds (1) and (2) based on the calibration curve.

[0122] The content of polymers was calculated from the peak area value measured by gel permeation chromatography (hereinafter referred to as "GPC"; apparatus: Tosoh Corporation HLC-8320GPC; column: Shodex LF-804 (3 columns); eluent: tetrahydrofuran) using a quantitative value calculated from a calibration curve.

[0123] The weight average molecular weight (Mw) of the polymer was calculated from the elution time in the measurement by GPC (apparatus: Tosoh Corporation HLC-8320GPC, column: Shodex LF-804 (3 columns), eluent: tetrahydrofuran) using a calibration curve with standard polystyrene.

[0124] <Example 5-1> [Process 1] In a 100 mL glass flask equipped with a Dean-Stark, 20.1 g (147 mmol) of 3-hydroxysulfolane, 103.1 g (1.0 mol) of methyl methacrylate, and 0.12 g of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (hereinafter referred to as "HO-TEMPO") were added, and the mixture was heated to reflux and the moisture in the solution was removed by the Dean-Stark. Next, 1.5 g (4 mmol) of tetrabutoxytitanium was added, and the reaction solution was heated to reflux at an internal temperature of 100 to 110 ° C while blowing air at 20 mL / min. The mixture was stirred for 2.5 hours while removing the methanol generated by the reaction by azeotropy with methyl methacrylate using the Dean-Stark. The amount of the mixture of methanol and methyl methacrylate extracted during this time was 45.8 g. The reaction rate by GC analysis was 91%. After cooling to room temperature, 1.6 g of water and 6.9 g of Celite were added and stirred for 1 hour. The resulting mixture was filtered under reduced pressure using filter paper. GPC analysis and Mw measurement showed that the Mw was 4.6×10 5 A high molecular weight component was detected at 1.15% by mass.

[0125] [Process 2] To the obtained filtrate, 30 mL of toluene was added, 15 mL of water was added to wash the organic layer, and the aqueous layer was drained using a separatory funnel. Then, 20 mL of water was added to wash the organic layer, and the aqueous layer was drained using a separatory funnel. Next, 24 g of hexane was added and stirred to precipitate a gel-like polymer. After adding magnesium sulfate to dry, the mixture was filtered under reduced pressure using filter paper, and the filtrate was concentrated using an evaporator to obtain 22.1 g of crude 3-sulfolanyl methacrylate. As a result of GPC analysis, no polymers with a molecular weight of 5000 or more were detected. 66.2 g of 2-propanol and 33.1 g of heptane were added to the obtained crude 3-sulfolanyl methacrylate, and the mixture was cooled with stirring. When the temperature dropped below 20°C, seed crystals were added to precipitate crystals. The obtained crystals were filtered, washed with heptane and water, and dried under reduced pressure to obtain 12.9 g of purified 3-sulfolanyl methacrylate. As a result of GPC analysis, no high molecular weight substances with a molecular weight of 5000 or more were detected.

[0126] <Example 5-2> [Process 1] In a 3L glass flask equipped with a stirrer, thermometer, and Dean-Stark, 351g (2.6mol) of 3-hydroxysulfolane, 1770g (17.7mol) of methyl methacrylate, and 2.2g of HO-TEMPO were added, and the mixture was heated to reflux and the moisture in the solution was removed by the Dean-Stark method. Next, 26g (77mmol) of tetrabutoxytitanium was added, and the reaction solution was heated to reflux at an internal temperature of 100-110°C while blowing in air at 20mL / min. The mixture was stirred for 8 hours while removing the methanol generated by the reaction by azeotropy with methyl methacrylate using the Dean-Stark method. The amount of the mixture of methanol and methyl methacrylate extracted during this time was 902g. The reaction rate was 88% by GC analysis. After cooling to room temperature, 28g of water and 121g of Celite were added and stirred for 1 hour, and the resulting mixture was filtered under reduced pressure using filter paper. GPC analysis and Mw measurement were performed, and the Mw was 4.0×10 5 A high molecular weight component was detected at 0.08% by mass.

[0127] [Process 2] Toluene (900 mL) was added to the obtained filtrate, and water (200 mL) was added to wash the organic layer, and 242 g of the aqueous layer was separated. Next, water (200 mL) was added to wash the organic layer, and 204 g of the aqueous layer was separated. Next, hexane (650 mL) was added and stirred to precipitate a gel-like polymer. After adding magnesium sulfate to dry, the mixture was filtered under reduced pressure using filter paper, and the filtrate was concentrated using an evaporator to obtain 406 g of crude 3-sulfolanyl methacrylate. As a result of GPC analysis, no polymers with a molecular weight of 5000 or more were detected. The obtained crude 3-sulfolanyl methacrylate was kept at 26°C, and 1181g of 2-propanol and 592g of heptane were added and cooled with stirring. When the temperature dropped below 20°C, seed crystals were added to precipitate crystals. The obtained crystals were filtered, washed with heptane and water, and dried under reduced pressure to obtain 219g of purified 3-sulfolanyl methacrylate. As a result of GPC analysis, no high molecular weight substances with a molecular weight of 5000 or more were detected.

[0128] <Example 5-3> [Process 1] In a 10L glass separable flask equipped with a stirrer, thermometer, and Dean-Stark, 1394g (10.2mol) of 3-hydroxysulfolane, 7269g (72.6mol) of methyl methacrylate, and 4.4g of HO-TEMPO were added, and the mixture was heated to reflux and the moisture in the solution was removed by Dean-Stark. Next, 70g (0.2mol) of tetrabutoxytitanium was added, and the reaction solution was heated to reflux at an internal temperature of 100-110°C while blowing in air at 20mL / min. The mixture was stirred for 6 hours while removing the methanol generated by the reaction by azeotropy with methyl methacrylate using a Dean-Stark. The amount of the mixture of methanol and methyl methacrylate extracted during this time was 1477g. The reaction rate was 67% by GC analysis. The mixture was then cooled to 70°C or less, 35g (0.1mol) of tetrabutoxytitanium was added, and the reaction solution was heated to reflux at an internal temperature of 100-110°C while blowing in air at 20mL / min. The mixture was stirred for 7.5 hours while removing methanol produced by the reaction by azeotropy with methyl methacrylate using a Dean-Stark. The amount of the mixture of methanol and methyl methacrylate taken out during this period was 2081g. The reaction rate was 87% by GC analysis. The mixture was cooled again to 70°C or less, 3.5g (0.01mol) of tetrabutoxytitanium was added, and the reaction solution was heated to reflux at an internal temperature of 100-110°C while blowing in air at 20mL / min. The mixture was stirred for 3.5 hours, and the reaction rate was 87% by GC analysis. The amount of the mixture of methanol and methyl methacrylate taken out during this period was 525g. After cooling to 70°C or less, 16 g of water and 483 g of Celite were added and stirred for 1 hour. The resulting mixture was filtered under pressure using filter paper. GPC analysis and Mw measurement showed that the Mw was 4.2×10 5 A high molecular weight component was detected at 0.21% by mass.

[0129] [Process 2] To the obtained filtrate, 3000g of toluene was added, 812g of water was added to wash the organic layer, and 965g of the aqueous layer was separated. Next, 837g of water was added to wash the organic layer, and 852g of the aqueous layer was separated. Next, 2020g of hexane was added and stirred to precipitate a gel-like polymer. The polymer was removed by pressure filtration using filter paper, and the filtrate was concentrated using an evaporator to obtain 1641g of crude 3-sulfolanyl methacrylate. As a result of GPC analysis, no polymer with a molecular weight of 5000 or more was detected. The obtained crude 3-sulfolanyl methacrylate was kept at 22°C, and 4690g of 2-propanol and 2380g of heptane were added and cooled with stirring. When the temperature dropped below 17°C, seed crystals were added to precipitate crystals. The obtained crystals were filtered, washed with heptane and water, and dried under reduced pressure to obtain 1000g of purified 3-sulfolanyl methacrylate. As a result of GPC analysis, no high molecular weight substances with a molecular weight of 5000 or more were detected.

[0130] <Comparative Example 5-1> Using 20.0 g (147 mmol) of 3-hydroxysulfolane, 118.0 g (1.2 mol) of methyl methacrylate, 0.12 g of HO-TEMPO, and 0.7 g (4 mmol) of tetraethoxytitanium, step 1 was carried out in the same manner as in Example 5-1. The filtrate was subjected to GPC analysis and Mw measurement, and the Mw was 4.8×10 5 A high molecular weight component was detected at 0.29% by mass.

[0131] To the obtained filtrate, 30 mL of toluene was added, 15 mL of water was added to wash the organic layer, and the aqueous layer was drained using a separatory funnel. Then, 15 mL of water was added to wash the organic layer, and the aqueous layer was drained using a separatory funnel. Magnesium sulfate was added to dry the mixture, and then the mixture was filtered under reduced pressure using filter paper. The filtrate was concentrated using an evaporator to obtain 25.6 g of crude 3-sulfolanyl methacrylate. As a result of GPC analysis, 0.22% by mass of high molecular weight substances were detected. When 38.9 g of 2-propanol was added to this crude 3-sulfolanyl methacrylate, gel-like high molecular weight substances were precipitated, but 38.4 g of 2-propanol and 38.5 g of heptane were further added as they were, and when the temperature fell below 20 ° C., seed crystals were added to perform recrystallization, and 21.3 g of purified 3-sulfolanyl methacrylate was obtained. As a result of GPC analysis, 0.11% by mass of high molecular weight substances with a molecular weight of 5000 or more were detected.

[0132] In these examples, the results of Mw measurement and GPC analysis of the high molecular weight products in each step are shown in Table 2 below. In Table 2, "after step 1" refers to the time after the reaction was completed, "after step 2" refers to the time after a poor solvent was added to precipitate and remove high molecular weight substances and concentrate the solution, and "after recrystallization" refers to the analytical results of the purified 3-sulfolanyl methacrylate obtained by recrystallization purification. ND indicates not detected.

[0133] [Table 2]

[0134] As shown in the results in Table 2, the 3-sulfolanyl methacrylate obtained in Examples 5-1 to 5-3 was of high purity with no high molecular weight compounds having a molecular weight of 5,000 or more being detected. On the other hand, in Comparative Example 5-1 in which step 2 was not carried out, the obtained 3-sulfolanyl methacrylate contained 0.11% by mass of high molecular weight compounds having a molecular weight of 5,000 or more. These results show that high molecular weight components can be removed by precipitating them using a poor solvent in the purification process, and the content of high molecular weight components with a molecular weight of 5,000 or more can be reduced to 0.1 weight % or less. [Industrial Applicability]

[0135] According to the present embodiment, there are obtained a polymer having good solubility in a developer, a resist composition containing the polymer, and a method for producing a substrate having a pattern formed thereon using the resist composition. According to this embodiment, a sulfonyl group-containing (meth)acrylic acid ester having a reduced amount of high molecular weight components can be obtained. The (meth)acrylic acid ester of the present embodiment has a reduced content of polymers and is useful in a wide range of applications such as plastics, paints, adhesives, etc. In addition, it is suitable as a monomer constituting a polymer for a resist and is useful for improving lithography properties.

Claims

1. A polymer comprising a structural unit (1) based on a monomer represented by the following formula (1), and a structural unit (2) having an acid-leaving group, wherein the structural unit (2) comprises both a structural unit (2i) having an acid-leaving group containing an alicyclic hydrocarbon group, and a structural unit (2ii) having an acid-leaving group containing a monocyclic alicyclic hydrocarbon group, the content of the structural unit based on a monomer having a polycyclic structure is 35 mol % or less with respect to all structural units, the content of the structural unit (1) with respect to all structural units is 15 mol % or more with respect to all structural units, and the content of the structural unit (2) with respect to all structural units is 20 mol % or more with respect to all structural units. 【Chemistry 1】 In formula (1), R 1 represents a hydrogen atom or a methyl group; A 1 represents a linking group containing an ester bond or a single bond, provided that A 1 has no tertiary carbon atom; Z 1 A 1 and the carbon atom bonded to -SO 2 represents an atomic group which, together with the --, forms a sulfur-containing cyclic hydrocarbon group having 4 carbon atoms.

2. The polymer according to claim 1 , further comprising a structural unit (3) having a lactone skeleton.

3. 3. A resist composition comprising the polymer according to claim 1 or 2, and a compound that generates an acid when exposed to actinic rays or radiation.

4. 4. A method for producing a substrate having a pattern formed thereon, comprising the steps of: applying the resist composition according to claim 3 onto a surface to be processed of a substrate to form a resist film; exposing the resist film to light; and developing the exposed resist film with a developer.

Citation Information

Patent Citations

  • 3-hydroxysulfolane and method for producing its ester

    JP2007153763A

  • Photoresist composition and method for deep UV

    JP2008521039A

  • Acrylic acid ester derivative, polymer compound, and photoresist composition

    JP2011184390A

  • Salt for acid generator, resist composition and method for producing resist pattern

    JP2012153662A

  • Resist composition and method for producing resist pattern

    JP2012234166A